Cancer treatment fatigue and nutritional awareness in cancer patients: a latent profile analysis and predictors - Meng, Qinhong; Du, Yuxuan; Tan, Qiaoxiu; He, Feifei; Miao, Haojun (Frontiers in Nutrition, 2026)
PurposeCancer requires long-term treatment, which imposes significant energy expenditure on the body, often exacerbating cancer-related fatigue among patients. Previous studies, adopting a variable-centered approach, have confirmed the relationship between cancer-related fatigue and nutrition management but have overlooked the relationship between cancer treatment fatigue and nutritional awareness, as well as their heterogeneity.MethodsFrom July to August 2025, we recruited 570 cancer patients using convenience sampling and employed latent profile analysis, single-variable analysis, and multivariable logistic regression to investigate the heterogeneity of cancer treatment fatigue and nutritional awareness, along with their influencing factors. Participants responded to measurement items related to variables such as cancer treatment fatigue, nutritional awareness, death anxiety, and cancer-specific loneliness, as well as provided necessary sociodemographic information.ResultsThree profiles were identified: (1) High Cancer Treatment Fatigue–Low Nutritional Awareness (14.6%), characterized by severe fatigue and minimal attention to diet; (2) Moderate Cancer Treatment Fatigue–Moderate Nutritional Awareness (68.2%) as the largest and relatively balanced group; and (3) Low Cancer Treatment fatigue–High Nutritional awareness (17.2%), showing adaptive physical and behavioral traits. Younger age, lower education, smoking, and alcohol use were associated with membership in the high-fatigue/low-awareness group (p < 0.05).ConclusionDistinct fatigue–nutrition coexistence patterns were demonstrated in oncology patients, suggesting that fatigue severity is closely intertwined with nutritional awareness. These findings provide evidence for incorporating personalized nutritional counseling and psychological fatigue-management programs into integrative cancer care to improve quality of life and treatment adherence.